Peer Coaching and Motivational Interviewing in Postsecondary Settings: Connecting Retention Theory with Practice. Issue 3 (23rd June 2018) - Warner, Zachary; Neater, William; Clark, Lauren; Lee, Jon
Abstract : Academic coaching is growing as a form of retention support, but questions surrounding what coaching should be continue to limit its potential. We argue that a resolution lies in increasing alignment between coaching practice, retention theory, and motivation, and that peer-led coaching guided by motivational interviewing offers a potentially unique blend of theory and practicality. Using phenomenological analysis procedures, we explore the experiences of a cohort of peer coaches to track changes in their perceived role and the skills they found most important to their success. Findings suggest peer coaches utilizing a framework guided by motivational interviewing came to view themselves as facilitators of change who nurtured intrinsic motivation by relying on their ability to form meaningful relationships with the students they served.